Implementasi Auto Ticketing pada Sistem Pelaporan Gangguan Provider Secara Otomatis di Perusahaan Penyedia Jasa Layanan Internet (ISP) - Ruci Antassani; Setiyono Setiyono (Yayasan Literasi Sains Indonesia, 2026)
The growing number of internet service providers (ISPs) in Indonesia has made the business sector increasingly challenging, and all ISPs are competing to innovate and provide the best service to their customers in order to retain existing customers and attract new ones. One innovation that ISPs can implement is to provide services that are oriented towards customer satisfaction and pamper their customers. One way to do this is by providing an auto-ticketing service when there is a disruption to the customer's internet connection. This eliminates the need for customers to manually contact the ISP's service complaint team to report the disruption, as this can be done automatically. Evaluation results show that the auto-ticketing system can speed up the disruption process carried out by ISP officers by 40% and improve the effectiveness and efficiency of ISP operations. Thus, this system offers an innovative solution for ISPs in improving service quality and customer satisfaction, thereby achieving the goal of retaining existing customers and attracting new ones.